Designing Motorcycle Security System Using E-KTP Sensor and SMS Gateway - Juani Khuswara Maulidin; Abrar Hiswara; Rafika Sari (PIKSEL : Penelitian Ilmu Komputer Sistem Embedded and Logic, 2021)
Motorcycle demand is increasing as well as the cases of vehicle theft in Indonesia. Not only increase theft cases, number of new modes of theft of the motorcycle is also increase. According to the Statistics Supervisory Agency (BPS) data from 2015 to 2018, the data on the number of motorcycles is increasing, starting every year around 126,508,776 motorcycles are sold in Indonesia. In Indonesia, it is estimated that hundreds of motorbikes are stolen every month. How is the feasibility of motorcycle safety devices and the accuracy of the RFID module. Creating a motorcycle security system using a microcontroller-based RFID-RC522 module that can be read accurately and can be monitored in real time using received SMS and test the feasibility of a motorcycle safety device that can be monitored via cellphone. Making this tool using the Prototype method. The prototype is a development method from the previous system. The results of this research are in accordance with the analysis and design that has been made to get the result of an E-KTP-based motorcycle safety device to increase the security of personal items because this device can activate and deactivate motorcycles by using SMS. This tool can also help the community in maintaining security around the surrounding environment so that they can add a double security system to motorcycle vehicles.